The longitudinal relation between violence exposure in daily life, hostile automatic thoughts, and cyber‐aggression. Issue 2 (5th November 2022) - Zhu, Wenfeng; Sun, Lindan; Lu, Dongxue; Li, Chenxing; Tian, Xue
Abstract: Cyber‐aggression is a serious social problem worldwide. Its risks have been frequently explored, and violence exposure in daily life has been regarded as an important risk factor of cyber‐aggression. However, the longitudinal association between violence exposure in daily life and cyber‐aggression has not yet been examined, and the mechanisms underlying the link between violence exposure and cyber‐aggression remain largely unclear. Based on the General Aggression Model and Script Theory, we explored the circular relation between violence exposure in daily life, hostile automatic thoughts, and cyber‐aggression. The current study adopted a longitudinal design to address these issues among 941 college students. The results indicated violence exposure in daily life predicted hostile automatic thoughts and cyber‐aggression 6 months later; hostile automatic thoughts predicted violence exposure and cyber‐aggression 6 months later; and cyber‐aggression predicted hostile automatic thoughts and violence exposure 6 months later. Moreover, each of them plays a mediating role in the association between the other two variables. These results support and expand the General Aggression Model and Script Theory that violence exposure, aggressive cognition, and aggression facilitate each other. This also provides theoretical guidance on reducing cyber‐aggression in daily life.